2016
DOI: 10.3758/s13421-016-0665-0
|View full text |Cite
|
Sign up to set email alerts
|

When high working memory capacity is and is not beneficial for predicting nonlinear processes

Abstract: Predicting the development of dynamic processes is vital in many areas of life. Previous findings are inconclusive as to whether higher working memory capacity (WMC) is always associated with using more accurate prediction strategies, or whether higher WMC can also be associated with using overly complex strategies that do not improve accuracy. In this study, participants predicted a range of systematically varied nonlinear processes based on exponential functions where prediction accuracy could or could not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…In function-learning experiments, participants learn to predict continuous output (y-values) from continuous input (x-values) variables. To do so, participants are presented with an input value (for example, a time point; Fischer and Holt, 2016), and then predict the corresponding outcome value.…”
Section: Introductionmentioning
confidence: 99%
“…In function-learning experiments, participants learn to predict continuous output (y-values) from continuous input (x-values) variables. To do so, participants are presented with an input value (for example, a time point; Fischer and Holt, 2016), and then predict the corresponding outcome value.…”
Section: Introductionmentioning
confidence: 99%
“…Mental set problem-solving tasks thus require flexibility in "overcoming" a suboptimal approach that is strongly activated by prior experience solving similar problems (i.e., "breaking" mental set). For example, Beilock and DeCaro (2007) found that high WMs were more likely to persist in using a complex problem-solving strategy despite the availability of simpler, more efficient alternatives (see Fischer & Holt, 2017, for a similar finding). Insight problems are problems that have a high probability of triggering a "faulty" initial problem representation (i.e., a representation that has a low probability of activating the knowledge needed to solve the problem; Ohlsson, 1992).…”
Section: Cognitive Flexibility and Working Memory Capacitymentioning
confidence: 88%
“…high WMs also persist in using suboptimal strategies (e.g., Beilock & DeCaro, 2007;Fischer & Holt, 2017;Richmond et al, 2015). To address this apparent inconsistency in the literature, the present research adopted a multifaceted view of WMC (Shipstead et al, 2014; see also Unsworth et al, 2014) to advance a novel theory of functional opponency in which different WMC mechanisms interact in ways that both support and constrain cognitive flexibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations